Mesoscale study of heavy rainfall of Delhi (MAUSAM, 1968)
In this study an attempt has been made to examine (1) The striking features of the spatial distribution of heavy rainfall (2 or more in 24 hours), during monsoon (June to October), at Delhi and neighbourhood (about 25 miles around the National Physical Laboratory (N.P.L) and (2) Any influence of the hillocks on the southeastern parts of Delhi and neighbourhood on the rainfall distribution.